Correlations between phylogenetic and functional diversity: mathematical artefacts or true ecological and evolutionary processes?. (2nd August 2013) - Pavoine, Sandrine; Gasc, Amandine; Bonsall, Michael B.; Mason, Norman W.H.
Abstract: Questions: Is phylogenetic diversity (PD) an accurate surrogate for functional diversity (FD)? How are FD:PD correlations affected by the diversity index used, covarying factors and/or the strength of the phylogenetic signal in ecological traits? Location: Field study, coastal marsh plain Mekhada, Algeria, complemented by simulated data. Methods: FD and PD indices might correlate simply because variation in species richness and evenness (referred to as co‐factors) influences both FD and PD values. We partition FD and PD indices into components influenced by species richness, evenness and species' (functional and phylogenetic) characteristics. When a simple partition was not found, comparison to null models was used to remove the effects of co‐factors. We examined correlations between ten FD and PD indices, among which several were shown to be connected using our mathematical partitioning approach and several were transformed by comparison with null models to control for effects of co‐factors. In doing this, FD values were calculated using simulated trait values with varying phylogenetic signal. We then selected a subset of complementary FD and PD indices in exploring the influence of environmental variables on diversity across 75 plant assemblages in Mekhada. Results: Altogether, mathematical partitioning and the comparison to null models successfully removed the effects of co‐factors when comparing FD and PD. For all indices affected by species richness, FD:PD correlations approached 1, irrespective of the trait evolution model used. In contrast, simulations showed that FD:PD correlations measured with indices unaffected by co‐factors decreased when the phylogenetic signal in traits decreased. Applied to plant assemblages in Mekhada, complementary diversity indices showed that, despite significant (but moderate) FD:PD correlation, FD but not PD was significantly correlated with the main stress gradient (salinity). Conclusions: From both our simulations and analysis of plant community diversity, PD was a poor surrogate for FD. In Mekhada, PD was also less correlated with environmental variables than FD. Species richness was found to be a better surrogate for FD than PD in identifying the ecological processes that distribute species along the salinity gradient. Abstract : Mathematical partitioning and comparisons to null models can successfully remove the effects of cofactors when comparing functional diversity (FD) and phylogenetic diversity (PD). However, simulations and real data analyses showed that PD turns out to generally be a poor surrogate for FD even in situations where functional traits display some degree of phylogenetic signal.